2020
DOI: 10.1021/acsomega.9b03534
|View full text |Cite
|
Sign up to set email alerts
|

Multistimuli-Responsive Fluorescent Organogelator Based on Triphenylamine-Substituted Acylhydrazone Derivative

Abstract: A new triphenylamine-based acylhydrazone derivative (TPAH-B8) was synthesized. TPAH-B8 could form organogels in cyclohexane through ultrasonic treatment. A typical gelation-induced fluorescence enhancement property was observed, which was attributed to the formation of J-aggregate in the gel state. More interestingly, TPAH-B8 exhibited multistimuli responsive behaviors. First, TPAH-B8 showed a solvatochromic effect, with the emission color changing from blue to cyan with the change in solvent from nonpolar cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In the presence of organic solvents, various gelators are able to form stable organogels, metallogels, and xerogels owing to the self-assembling of π-conjugated networks, as well as hydrogen and van der Waals forces between the moieties and the solvent. [94,95] However, matching these conditions requires the testing of a wide range of solvents with each supramolecular network to describe its functionality, as well as stability conditions and limitations. As an example, Yang et al reported that a coumarin-based Schiffbase gelator forms low-molecular-weight organogel networks in isopropanol, tert-amyl alcohol, n-butanol, and phenylamine, and acts as an ion detector (Figure 5B).…”
Section: Organogel-based Sensorsmentioning
confidence: 99%
“…In the presence of organic solvents, various gelators are able to form stable organogels, metallogels, and xerogels owing to the self-assembling of π-conjugated networks, as well as hydrogen and van der Waals forces between the moieties and the solvent. [94,95] However, matching these conditions requires the testing of a wide range of solvents with each supramolecular network to describe its functionality, as well as stability conditions and limitations. As an example, Yang et al reported that a coumarin-based Schiffbase gelator forms low-molecular-weight organogel networks in isopropanol, tert-amyl alcohol, n-butanol, and phenylamine, and acts as an ion detector (Figure 5B).…”
Section: Organogel-based Sensorsmentioning
confidence: 99%
“…The unique optical patterning and morphological perspectives of π-conjugated self-assembled molecular systems have recently created glimpses of curiosity due to constituting dynamically flexible noncovalent interactions (π ... π, hydrogen bonding, van der Waals forces), which respond sensibly toward various external stimuli (stress, heat, different analytes, etc.) mainly via tunable fluorescence and phase transition. , Among the ubiquitous analytes present in the environment, cyanide (CN – ) and nitroaromatic compounds (NAs) cause momentous ecological pollution via their uncontrolled release into the surroundings by industrial wastages and unauthorized terror activities. Importantly, binding of CN – with iron (Fe 3+ ) in metalloenzyme hampers the central respiratory system of the mammalian body, which ultimately causes instantaneous death .…”
Section: Introductionmentioning
confidence: 99%
“…mainly via tunable fluorescence and phase transition. 1,2 Among the ubiquitous analytes present in the environment, cyanide (CN − ) and nitroaromatic compounds (NAs) cause momentous ecological pollution via their uncontrolled release into the surroundings by industrial wastages and unauthorized terror activities. Importantly, binding of CN − with iron (Fe 3+ ) in metalloenzyme hampers the central respiratory system of the mammalian body, which ultimately causes instantaneous death.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Biomedical, foodstuff, and cosmetic applications have all exploited organogel technology. The self-assembly of small organogelator molecules occurs by the entrapment of tolerable volumes of solvents, providing beneficial characteristics for various applications. Self-assembled structures can introduce optoelectronic characteristics like enhancing emission and charge transfer. A supramolecular organogel can be described as a soft matter consisting of a viscoelastic non-flowing fluid due to the existence of an organogelator capable of self-assembling into three-dimensional supramolecular architectures. Those supramolecular architectures can be generated in a variety of morphologies, such as nanofeathers, nanoribbons, nanosheets, nanorods, and nanofibers. , Self-assembly of organogelators has interesting research in many fields, such as catalysis, sensors, pollutant removal, drug self-delivery, and tissue engineering.…”
Section: Introductionmentioning
confidence: 99%